2019
DOI: 10.1186/s12888-019-2092-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal variance among patients, next of kin and health care professionals towards the use of containment measures in three psychiatric hospitals in Switzerland

Abstract: Background In psychiatric treatment containment measures are used to de-escalate high-risk situations. These measures can be characterized by their immanent amount of coercion. Previous research could show that the attitudes towards different containment measures vary throughout countries. The aim of this study was to compare the attitudes towards containment measures between three study sites in Switzerland which differ in their clinic traditions and policies and their actual usage of these measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
1
Order By: Relevance
“…Most studies (n=42) reported on restraint and seclusion techniques. The pooled prevalence for coercive interventions was 47.8% (95% CI 0.38 to 0.57) with high heterogeneity (I 2 100.0%) in 12 studies136–147 (online supplementary file 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies (n=42) reported on restraint and seclusion techniques. The pooled prevalence for coercive interventions was 47.8% (95% CI 0.38 to 0.57) with high heterogeneity (I 2 100.0%) in 12 studies136–147 (online supplementary file 6).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies focused on coercion; one study examined prevalence of coercive measures141 and one study explored how the experience of staff might contribute to the use of restrictive practices 210. The attitudes of staff,142 144 211–222 patients145 223–226 and mixed groups143 168 227–230 towards coercion were explored in 25 studies, and 5 studies examined the process of coercive interventions139 140 231 232 and rules of engagement in caring for aggressive patients 233…”
Section: Resultsmentioning
confidence: 99%
“…However, other influencing factors should also be considered here. In particular, the attitudes of the staff members with respect to mechanical restraint and seclusion play a crucial role and can differ among the hospitals [ 51 55 ]. Here, the key focus is on the area of conflict between the staff’s risk-taking propensity and their respect for patient autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…First insights into the decision-making processes in clinical practice have led to a stronger focus on the subjective aspects involved in the use of coercion. These include not only the subjective experience of people affected by coercive interventions, [20][21][22] but also attitudes, personality traits and personal experiences of the mental health professionals involved. [23][24][25][26][27][28] The latter might be important with regard to the use of coercion for two main reasons: firstly, the subjective experiences of mental health professionals are a key element of interactions with people with mental disorders and might influence the escalation or de-escalation of potential conflictual situations.…”
Section: Introductionmentioning
confidence: 99%